Availability and Quality of Grief and Bereavement Care in Pediatric Intensive Care Units Around the World, Opportunities for Improvement - Grunauer, Michelle; Mikesell, Caley; Bustamante, Gabriela; Aronowitz, Danielle; Zambrano, Kevin; Icaza-Freire, Andrea P.; Gavilanes, Antonio W. D.; Barrera, Rafael; , the PICU-MIC Research Group; González, Jorge López; López-Herce, Jesús; Rossetti, Emanuele; et al. (Frontiers in Pediatrics, 2021)
Pediatric Intensive Care Units (PICUs) provide multidisciplinary care to critically ill children and their families. Grief is present throughout the trajectory of illness and can peak around the time of death or nondeath losses. The objective of this study was to assess how PICUs around the world implement grief and bereavement care (GBC) as part of an integrated model of care. This is a multicenter cross-sectional, prospective survey study. Questionnaires with multiple-choice and open-ended questions focusing on unit infrastructure, personnel, policies, limited patient data, and practices related to GBC for families and health care professionals (HCPs) were completed by on-site researchers, who were HCPs on the direct care of patients. PICU fulfillment of GBC goals was evaluated using a custom scoring based on indicators developed by the Initiative for Pediatric Palliative Care (IPPC). We compared average total and individual items fulfillment scores according to the respective country’s World Bank income. Patient characteristics and details of unit infrastructure were also evaluated as potential predictors of total GBC fulfillment scores. Statistical analysis included multilevel generalized linear models (GLM) with a Gaussian distribution adjusted by child age/gender and clustering by center, using high income countries (HICs) as the comparative reference. Additionally, we applied principals of content analysis to analyze and summarize open-ended answers to contextualize qualitative data. The study included 34 PICUs from 18 countries: HICs: 32.4%, upper middle-income countries (UMICs): 44.1%, low middle income and low-income countries (LMI/LICs): 23.5%). All groups reported some compliance with GBC goals; no group reported perfect fulfillment. We found statistically significant differences in GBC fulfillment scores between HICs and UMICs (specifically, HCP grief support), and between HICs and LMICs (specifically, family grief support and HCP grief support). PICUs world-wide provide some GBC, independent of income, but barriers include lack of financial support, time, and training, overall unit culture, presence of a palliative care consultation service, and varying cultural perceptions of child death. Disparities in GBC for families and HCPs exist and were related to the native countries’ income level. Identifying barriers to support families and HCPs, can lead to opportunities of improving GBC in PICUs world-wide.